ANALISIS PENGARUH KUALITAS PRODUK, HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUASAAN PELANGGAN DI MIE GACOAN TAMAN SISWA YOGYAKARTA - Wardani, Indriana Setya; Tuti, Dwi Utami Dias; Elyasa, Reka (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
The formulation of the problem in this study is whether the indicators of product quality, price and service quality affect customer satisfaction. The purpose of this research is to test whether product quality, price and service quality affect customer satisfaction. The data collection technique used is a questionnaire. The analytical method used in this study is a quantitative descriptive method. The analysis of this study used the SPSS application for all tests. From the results of testing the hypothesis it is known that the product quality and service quality variables have a significant overall effect on customer satisfaction at Mie Gacoan Tamansiswa Yogyakarta, while the price variable does not have an overall significant effect on customer satisfaction.